2021
DOI: 10.1111/ppc.12941
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of nursing students towards LGBT individuals and the affecting factors

Abstract: Purpose To determine the attitudes of nursing students towards LGBT (lesbian, gay, bisexual, and transgender) individuals and the affecting factors. Design and Method The universe of the research consisted of 500 students. The data collection tools used were “Demographic Data Form” and “Attitude towards Lesbians and Gay Men Scale (ATLG).” Findings Students' attitudes towards LGBT individuals are at a medium level. Male participants had more negative attitudes towards LGBT individuals. Practical Implications Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…In a recent study with nursing students in Turkey, male students reported having more discriminating attitudes towards LGBT individuals when compared to female students [ 8 ]. Various demographic factors (gender, race, and if they know an LGBT person) can be associated with attitudes that nursing students have toward LGBT individuals and their comfort with caring for them [ 8 , 9 , 10 ]. Research findings indicate that further exploration of this topic is needed [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study with nursing students in Turkey, male students reported having more discriminating attitudes towards LGBT individuals when compared to female students [ 8 ]. Various demographic factors (gender, race, and if they know an LGBT person) can be associated with attitudes that nursing students have toward LGBT individuals and their comfort with caring for them [ 8 , 9 , 10 ]. Research findings indicate that further exploration of this topic is needed [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various demographic factors (gender, race, and if they know an LGBT person) can be associated with attitudes that nursing students have toward LGBT individuals and their comfort with caring for them [ 8 , 9 , 10 ]. Research findings indicate that further exploration of this topic is needed [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in countries like Greece (Fradelos et al, 2022 ) and Taiwan (Wang et al, 2019 ) also reported that nursing students held positive attitudes toward LGBT patients. Another research, however, still noted only a medium-level attitude towards LGBT individuals among nursing students (Özdemir & Erenoğlu, 2022 ). Constant monitoring and assessment of students’ attitudes towards LGBT individuals may still be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps in our sample, females had more interest in and exposure to LGBT health needs and concerns. It has been reported that male nursing students had more unfavorable attitudes toward LGBT individuals (Özdemir & Erenoğlu, 2022 ). Another study conducted elsewhere noted that female primary care providers indicated a stronger inclination for additional training when contrasted with their male counterparts (Rowe et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of these disparities and contributing barriers is essential to providing culturally responsive care and developing effective interventions that improve outcomes in this vulnerable population (Özdemir & Erenoğlu, 2022). Culturally responsive care moves beyond gained knowledge and skills to implementation by valuing diversity and responding to the needs of others across practice settings (Markey, 2021).…”
mentioning
confidence: 99%